Remaking citizenship in Hong Kong : community, nation and the global city - Ku, Agnes S. M.; Pan, Yi (RoutledgeCurzon studies in Asia's transformations., 2004)
This book provides a detailed comparative account of the development of citizenship and civil society in Hong Kong from its time as a British colony to its current status as a special autonomous region of China.